2014
DOI: 10.1136/neurintsurg-2014-011185
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of symptomatic intracranial stenosis using balloon mounted coronary stents: a single center experience

Abstract: This study suggests that BMCS may benefit patients with symptomatic intracranial stenosis who experience stroke or transient ischemic attack in spite of best medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Our decision to use BMCS for the treatment of SIVBS was supported by clinically based experiences of some reported case series 17,18 . Moreover, the use of BMCS Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our decision to use BMCS for the treatment of SIVBS was supported by clinically based experiences of some reported case series 17,18 . Moreover, the use of BMCS Fig.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 In another series of patients treated with BMCS for intracranial stenosis in both anterior circulation intracranial stenosis and SIVBS, Durst et al reported an overall peri-procedural morbidity of 7,1%, but registered higher complication rates in posterior circulation procedures than in anterior circulation. 18 Analyzing data from 3 studies about balloon-mounted stent implantation, 17,28,29 Durst et al reported an average periprocedural morbidity of 7.4% in 339 patients (range 5,6-22,7%). However, also in these series both anterior and posterior intracranial stenoses were pooled together.…”
Section: Early Outcomesmentioning
confidence: 99%
“…The first study by Durst et al utilized only balloon-mounted coronary stents, and had a relatively low incidence of periprocedural morbidity and mortality (7.1%) as well as long-term incidence of recurrent CVA (9.5%) (7). In contrast, Tarlov and colleagues demonstrated a much higher risk of intervention, both in increased morbidity and mortality in the periprocedural stage (22%) as well as long-term recurrent CVA (21.95%).…”
Section: Discussionmentioning
confidence: 99%
“…Select series of patients with intracranial arterial stenosis experiencing repeated strokes after initiation of best medical therapy suggest that this may be a beneficial alternative. 8 This may also be a favorable therapeutic option in patients who cannot achieve the goals of best medical therapy, including blood pressure, low-density lipoprotein, and diabetes control, along with weight reduction and exercise. Further studies are indicated to determine the optimal management in patients with repeated strokes attributable to significant intracranial arterial stenosis in the setting of failed primary medical therapy.…”
Section: Long-term Outcomes Of a Randomized Clinicalmentioning
confidence: 99%